An enzyme-linked immunosorbent assay for detection of Theileria parva antibodies in cattle using a recombinant polymorphic immunodominant molecule - Katende, J.; Morzaria, S.P.; Toye, Philip G.; Skilton, Robert A.; Nene, Vishvanath M.; Nkonge, C.; Musoke, A.J. (Springer, 1998)
Field and experimental bovine infection sera were used in immunoblots of sporozoite and schizont lysates of Theileria parva to identify candidate diagnostic antigens. Four parasite antigens of Mr 67,000 (p67), 85,000 (the polymorphic immunodominant molecule, PIM), 104,000 (p104), and 150,000 (p150) were selected for a more detailed anlysis. The p67 and p104 antigens were present only in the sporozoite lysates, whereas PIM and p150 were found in both sporozoite and schizont lysates. The four antigens were expressed as recombinant fusion proteins and were compared with each other in an enzyme-linked immunosorbent assay (ELISA) and in the whole-schizont-based indirect fluorescent antibody test (IFAT) in terms of their ability to detect antibodies in sera of experimentally infected cattle. The PIM-based ELISA provided a higher degree of sensitivity and specificity than did the ELISA using the other three recombinant antigens or the IFAT. Further evaluation of the PIM-ELISA using experimental sera derived from cattle infected with different hemoparasites and field sera from endemic and nonendemic T. parva areas showed that the assay had a sensitivity of > 99 percent and a specificity of between 94 percent and 98 percent.